2004
DOI: 10.1161/01.hyp.0000148460.95060.f2
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure During Recovery From Exercise and the Risk of Acute Myocardial Infarction in Middle-Aged Men

Abstract: Abstract-We prospectively assessed the association of systolic blood pressure (SBP) after exercise with the risk of an acute myocardial infarction. Limited information exists currently on the role of SBP during recovery period with the risk of acute myocardial infarction. SBP was measured every 2 minutes during and after a progressive cycle ergometer exercise test in a representative sample of 2336 men (aged 42 to 61 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
105
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 51 publications
8
105
2
1
Order By: Relevance
“…An early elevation in SBP during exercise provides further prognostic information toward cardiovascular outcomes and is known to be an important marker of various cardiovascular diseases, including incident hypertension, myocardial infarction, and stroke, as well as cardiovascular mortality in persons without overt coronary artery disease (CAD) 2, 3, 4, 5…”
mentioning
confidence: 99%
“…An early elevation in SBP during exercise provides further prognostic information toward cardiovascular outcomes and is known to be an important marker of various cardiovascular diseases, including incident hypertension, myocardial infarction, and stroke, as well as cardiovascular mortality in persons without overt coronary artery disease (CAD) 2, 3, 4, 5…”
mentioning
confidence: 99%
“…This is in contrast to several other investigators who have found a relation between recovery blood pressure level and hypertension as well as myocardial infarction and cardiovascular death. 8,9,16,25,26 We had several missing values for SBP 4 min after exercise that can make the comparison with other variables difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to find a suitable predictor for future hypertension and cardiovascular disease is to evaluate the blood pressure level at recovery. 8,16 The diversity in predictive values could be explained by differences in exercise test methods, the definition of the hypertensive reaction and study populations. Several investigations have been performed on healthy young or middle-aged males.…”
Section: Introductionmentioning
confidence: 99%
“…In a populationbased sample of 1033 normotensive Japanese men, for example, exercise-induced increase in BP was a strong determinant of future hypertension (13). Both HR reactivity (27)(28)(29) and BP reactivity (14,15) in response to graded exercise are potent indicators of cardiovascular outcomes. Taken together, these data suggest that performing actigraphy and ABPM concomitantly may further enhance the prognostic information already contained in ambulatory BP recordings.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in otherwise healthy individuals, the extent of increase in BP with physical activity is an independent predictor of incident hypertension (13). In those who are referred for exercise testing, BP reactivity is a marker of cardiovascular outcomes (14,15). Thus, it is logical to postulate that a higher level of physical activity over the long-term would foster a greater level of cardiovascular health.…”
mentioning
confidence: 99%